PENGARUH AUDIT TENURE DAN PROFITABILITAS TERHADAP AUDIT REPORT LAG PADA SEKTOR CONSUMER CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA (Studi Empiris Tahun 2020 – 2023) - Muhammad Irfan Nugraha; Imam Ghozali (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of audit tenure and profitability on audit report lag in consumer cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2023 period. The independent variables used are audit tenure (measured by a dummy variable) and profitability (proxied by Return on Assets). This study also includes firm size and pandemic conditions as control variables.The sampling method used was purposive sampling, resulting in 280 observations from 73 companies after the exclusion of outliers. Data analysis was performed using panel data regression with the Fixed Effect Model (FEM) and Panel-Corrected Standard Errors (PCSE) estimation to address heteroscedasticity and autocorrelation issues.The results show that simultaneously, audit tenure, profitability, firm size, and pandemic conditions significantly affect audit report lag. Partially, profitability has a significant negative effect on audit report lag, indicating that companies with high financial performance tend to accelerate the publication of audited financial statements to mitigate information asymmetry in accordance with agency theory. Conversely, audit tenure is not proven to have a significant effect on audit report lag. Additional tests (t-test) show a significant difference in audit duration between the pandemic and post-pandemic periods, where audit duration actually increased in the pandemic period.